Combustion aerosols from mineral oil industrial fires: Physicochemical characterization and toxicity in bronchial epithelial cells at the air-liquid interface - C. Méausoone; T. Rogez-Florent; C. Castilla; L. Chevalier; C. Bouzar; P. Cardinael; T. Legeard; S. Tisse; J. Yon; F. Portet-Koltalo; E. Varea; B. Patte-Rouland; et al. (Environmental Pollution, 2026)

Gill ionocytes of the Lake Magadi tilapia (Oreochromis Alcolapia grahami), an extremophilic teleost native to a highly alkaline environment - Jonathan M. Wilson; Chris M. Wood; Pierre Laurent; Claudine Chevalier; Patrícia G. Ferreira; Kevin V. Brix; Gudrun DeBoeck; Harold L. Bergman; Adalto Bianchini; Lucas Feijó Bianchini; John N. Maina; Ora E. Johannsson; et al. (Cell and Tissue Research, 2026)

Paul Tapponnier, deciphering the Earth's crust deformation history in the rocks and landscapes - A. Replumaz; J.-P. Avouac; M.-L. Chevalier; Y. Klinger; C. Lasserre; P.H. Leloup; J. Liu-Zeng; G. Peltzer; J. van der Woerd; X. Xu (Tectonophysics, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

WITHDRAWN: Paul Tapponnier, deciphering the Earth's crust deformation history in the rocks and landscapes - A. Replumaz; J.-P. Avouac; M.-L. Chevalier; Y. Klinger; C. Lasserre; P.H. Leloup; J. Liu-Zeng; G. Peltzer; J. van der Woerd; X. Xiwei (Tectonophysics, 2026)

Cellulose nanofibers as stabilizer of Pickering emulsions and reinforcement of pectin films covering tomatoes - Raquel Costa Chevalier; Jorge M. Vieira; Joana T. Martins; Rosiane Lopes Cunha; António A. Vicente (Food and Bioproducts Processing, 2026)

Spondias tuberosa Arruda (Anacardiaceae) ethanolic leaf extract as a source of natural products inhibiting quorum sensing and pyocyanin production in planktonic Pseudomonas aeruginosa - A.S. Tareau; P.E. Bodet; J.R. Guedes da Silva Almeida; M. Barreau; O. Lesouhaitier; A. Tahrioui; R. Gonçalves de Oliveira Junior; R. Grougnet; P. Sitarek; L. Quintans-Junior; K. Baranger; S. Chevalier; et al. (Phytochemistry Letters, 2025)

No deformation propagation outward of the plateau across the Yalong Thrust Belt in Southeast Tibet - P. Pitard; A. Replumaz; P.H. Leloup; M.-L. Chevalier; S. Wang; M. Bai; X. Ou; M. Bernet; M. Balvay; E.R. Sobel; A. Vezinet; C. Gautheron; et al. (Tectonophysics, 2025)

Functional and nutritional properties of fava bean ingredients processed by extrusion - I. Jebalia; G. Della Valle; D. Dupont; V. Santé-Lhoutellier; H. Rabesona; G. Henry; S. Chevalier; M. Guillevic; A. Germain; G. Chesneau; M. Kristiawan (Food Research International, 2025)

P24-08 Chronic exposure to low-doses of maneb and manganese alters differentiation and lipid accumulation in hepatocytes in vitro - L. Chevalier; S. Pierre; M. Dufresne; M. Marceau; C. Pinteur; A. Corlu; B. Le Magueresse-Battistoni; P. Loyer (Toxicology Letters, 2025)

P08-12 Exposure to commercial copper-based nanopesticide reshapes chironomid-associated microbiota and alters host life history traits - L. Evariste; T. Moura; F. Chapeau; F. Candaudap; G. Le Roux; L. Chevalier; C. Larue; M. Barret; E. Pinelli; E. Houdeau; L. Gauthier; B. Lamas; et al. (Toxicology Letters, 2025)

Chronic use of cannabidiol (CBD) and cannabidiolic acid (CBDA) in horses does not alter their metabolic profile - J.J. Wakshlag; J.M. Chevalier; G.B. Pearson; M. Cercone (Journal of Equine Veterinary Science, 2025)

Long-term impact of embryonic exposure to ethinylestradiol and clotrimazole on behavior and neuroplasticity in zebrafish (Danio rerio) - M. Blanc-Legendre; L. Guillot; L. Chevalier; C. Malleret; K. Le Menach; P. Pardon; H. Budzinski; F. Brion; S. Sire; P. Coumailleau; T.D. Charlier; E. Pellegrini; et al. (Environmental Toxicology and Pharmacology, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Influence of the Rhone River intrusion on microplastic distribution in the Bay of Marseille - A. Alcaïno; L. Vidal; L. Licari; C. Paillès; S. Conrod; J. Dauvier; C. Chevalier; C. Pinazo; M. Grelaud; P. Ziveri (Regional Studies in Marine Science, 2024)

Water column distribution of zooplanktonic size classes derived from in-situ plankton profilers: Potential use to contextualize contaminant loads in plankton - B. Espinasse; M. Pagano; S.L. Basedow; C. Chevalier; D. Malengros; F. Carlotti (Marine Pollution Bulletin, 2023)

Applying landscape metrics to species distribution model predictions to characterize internal range structure and associated changes - Amelia Curd; Mathieu Chevalier; Mickaël Vasquez; Aurélien Boyé; Louise B. Firth; Martin P. Marzloff; Lucy M. Bricheno; Michael T. Burrows; Laura E. Bush; Céline Cordier; Andrew J. Davies; J. A. Mattias Green; et al. (Global Change Biology, 2023)
Distributional shifts in species ranges provide critical evidence of ecological responses to climate change. Assessments of climate‐driven changes typically focus on broad‐scale range shifts (e.g. poleward or upward), with ecological consequences at regional and local scales commonly overlooked. While these changes are informative for species presenting continuous geographic ranges, many species have discontinuous distributions—both natural (e.g. mountain or coastal species) or human‐induced (e.g. species inhabiting fragmented landscapes)—where within‐range changes can be significant. Here, we use an ecosystem engineer species ( Sabellaria alveolata ) with a naturally fragmented distribution as a case study to assess climate‐driven changes in within‐range occupancy across its entire global distribution. To this end, we applied landscape ecology metrics to outputs from species distribution modelling (SDM) in a novel unified framework. SDM predicted a 27.5% overall increase in the area of potentially suitable habitat under RCP 4.5 by 2050, which taken in isolation would have led to the classification of the species as a climate change winner. SDM further revealed that the latitudinal range is predicted to shrink because of decreased habitat suitability in the equatorward part of the range, not compensated by a poleward expansion. The use of landscape ecology metrics provided additional insights by identifying regions that are predicted to become increasingly fragmented in the future, potentially increasing extirpation risk by jeopardising metapopulation dynamics. This increased range fragmentation could have dramatic consequences for ecosystem structure and functioning. Importantly, the proposed framework—which brings together SDM and landscape metrics—can be widely used to study currently overlooked climate‐driven changes in species internal range structure, without requiring detailed empirical knowledge of the modelled species. This approach represents an important advancement beyond predictive envelope approaches and could reveal itself as paramount for managers whose spatial scale of action usually ranges from local to regional.

Genomic analysis of a parasite invasion: Colonization of the Americas by the blood fluke Schistosoma mansoni - Roy N. Platt; Winka Le Clec'h; Frédéric D. Chevalier; Marina McDew‐White; Philip T. LoVerde; Rafael Ramiro de Assis; Guilherme Oliveira; Safari Kinung'hi; Amadou Garba Djirmay; Michelle L. Steinauer; Anouk Gouvras; Muriel Rabone; et al. (Molecular Ecology, 2022)
Schistosoma mansoni , a snail‐borne, blood fluke that infects humans, was introduced into the Americas from Africa during the Trans‐Atlantic slave trade. As this parasite shows strong specificity to the snail intermediate host, we expected that adaptation to South American Biomphalaria spp. snails would result in population bottlenecks and strong signatures of selection. We scored 475,081 single nucleotide variants in 143 S. mansoni from the Americas (Brazil, Guadeloupe and Puerto Rico) and Africa (Cameroon, Niger, Senegal, Tanzania, and Uganda), and used these data to ask: (i) Was there a population bottleneck during colonization? (ii) Can we identify signatures of selection associated with colonization? (iii) What were the source populations for colonizing parasites? We found a 2.4‐ to 2.9‐fold reduction in diversity and much slower decay in linkage disequilibrium (LD) in parasites from East to West Africa. However, we observed similar nuclear diversity and LD in West Africa and Brazil, suggesting no strong bottlenecks and limited barriers to colonization. We identified five genome regions showing selection in the Americas, compared with three in West Africa and none in East Africa, which we speculate may reflect adaptation during colonization. Finally, we infer that unsampled populations from central African regions between Benin and Angola, with contributions from Niger, are probably the major source(s) for Brazilian S. mansoni . The absence of a bottleneck suggests that this is a rare case of a serendipitous invasion, where S. mansoni parasites were pre‐adapted to the Americas and able to establish with relative ease.

Application of the anatomical fiducials framework to a clinical dataset of patients with Parkinson’s disease - Mohamad Abbass; Greydon Gilmore; Alaa Taha; Ryan Chevalier; Magdalena Jach; Terry M. Peters; Ali R. Khan; Jonathan C. Lau (Brain Structure and Function, 2022)
Establishing spatial correspondence between subject and template images is necessary in neuroimaging research and clinical applications such as brain mapping and stereotactic neurosurgery. Our anatomical fiducial (AFID) framework has recently been validated to serve as a quantitative measure of image registration based on salient anatomical features. In this study, we sought to apply the AFIDs protocol to the clinic, focusing on structural magnetic resonance images obtained from patients with Parkinson’s disease (PD). We confirmed AFIDs could be placed to millimetric accuracy in the PD dataset with results comparable to those in normal control subjects. We evaluated subject-to-template registration using this framework by aligning the clinical scans to standard template space using a robust open preprocessing workflow. We found that registration errors measured using AFIDs were higher than previously reported, suggesting the need for optimization of image processing pipelines for clinical grade datasets. Finally, we examined the utility of using point-to-point distances between AFIDs as a morphometric biomarker of PD, finding evidence of reduced distances between AFIDs that circumscribe regions known to be affected in PD including the substantia nigra. Overall, we provide evidence that AFIDs can be successfully applied in a clinical setting and utilized to provide localized and quantitative measures of registration error. AFIDs provide clinicians and researchers with a common, open framework for quality control and validation of spatial correspondence and the location of anatomical structures, facilitating aggregation of imaging datasets and comparisons between various neurological conditions.

Buffering effects of soil seed banks on plant community composition in response to land use and climate - Jan Plue; Hans Van Calster; Inger Auestad; Sofía Basto; Renée M. Bekker; Hans Henrik Bruun; Richard Chevalier; Guillaume Decocq; Ulf Grandin; Martin Hermy; Hans Jacquemyn; Anna Jakobsson; et al. (Global Ecology and Biogeography, 2021)
Aim Climate and land use are key determinants of biodiversity, with past and ongoing changes posing serious threats to global ecosystems. Unlike most other organism groups, plant species can possess dormant life‐history stages such as soil seed banks, which may help plant communities to resist or at least postpone the detrimental impact of global changes. This study investigates the potential for soil seed banks to achieve this. Location Europe. Time period 1978–2014. Major taxa studied Flowering plants. Methods Using a space‐for‐time/warming approach, we study plant species richness and composition in the herb layer and the soil seed bank in 2,796 community plots from 54 datasets in managed grasslands, forests and intermediate, successional habitats across a climate gradient. Results Soil seed banks held more species than the herb layer, being compositionally similar across habitats. Species richness was lower in forests and successional habitats compared to grasslands, with annual temperature range more important than mean annual temperature for determining richness. Climate and land‐use effects were generally less pronounced when plant community richness included seed bank species richness, while there was no clear effect of land use and climate on compositional similarity between the seed bank and the herb layer. Main conclusions High seed bank diversity and compositional similarity between the herb layer and seed bank plant communities may provide a potentially important functional buffer against the impact of ongoing environmental changes on plant communities. This capacity could, however, be threatened by climate warming. Dormant life‐history stages can therefore be important sources of diversity in changing environments, potentially underpinning already observed time‐lags in plant community responses to global change. However, as soil seed banks themselves appear, albeit less, vulnerable to the same changes, their potential to buffer change can only be temporary, and major community shifts may still be expected.

Sizes, condition factors and sex ratios of the scattered populations of the small cichlid fish, Alcolapia grahami, that inhabits the lagoons and sites of Lake Magadi (Kenya), one of the most extreme aquatic habitat on Earth - John N. Maina; Geraldine D. Kavembe; Michael B. Papah; Reatlegile Mashiteng; Chris M. Wood; Adalto Bianchini; Lucas F. Bianchini; Harold L. Bergman; Ora E. Johannsson; Piere Laurent; Claudine Chevalier; Rodi O. Ojoo (Environmental Biology of Fishes, 2019)

A Practical Methodology to Screen Oil Recovery Processes Involving Spontaneous Imbibition - T. Chevalier; J. Labaume; A. Delbos; T. Clemens; V. M. Waeger; B. Bourbiaux; M. Fleury (Transport in Porous Media, 2019)

A high‐resolution record of Holocene climate and vegetation dynamics from the southern Cape coast of South Africa: pollen and microcharcoal evidence from Eilandvlei - Lynne J. Quick; Brian M. Chase; Michael Wündsch; Kelly L. Kirsten; Manuel Chevalier; Roland Mäusbacher; Michael E. Meadows; Torsten Haberzettl (Journal of Quaternary Science, 2018)
The southern Cape is a particularly dynamic region of South Africa in terms of climate change as it is influenced by both temperate and tropical circulation systems. This paper presents pollen and microcharcoal data generated from a sediment core extracted from the coastal lake Eilandvlei spanning the last ∼8900 years. With an average sample resolution of 57 years, this record represents the highest resolution record of Holocene vegetation change from the region. The data indicate that cool, seasonal and moderately dry conditions characterized the Wilderness Embayment from ∼8900 to 8000 cal a BP . Afrotemperate forests expanded from ∼8000 cal a BP until 4700 cal a BP . This humid period is followed by indications of more arid and seasonal conditions until 3500 cal a BP . A long‐term increase in forest taxa suggests steadily increasing moisture availability across the late Holocene. Strong affinities are noted with records from more tropical regions of South Africa, suggesting that tropical systems are of importance in maintaining higher moisture availability in the region. An important mechanism of climate change is the Agulhas Current, which transmits what appears to be a localized signal of tropical variability to the southern Cape coast.

A population of mitochondrion-rich cells in the pars recta of mouse kidney - M. S. Forbes; B. A. Thornhill; C. I. Galarreta; R. L. Chevalier (Cell and Tissue Research, 2016)

Determining the drivers of long‐term aridity variability: a southern African case study - Manuel Chevalier; Brian M. Chase (Journal of Quaternary Science, 2016)
This paper highlights the importance of differentiating between precipitation amount and moisture availability (‘humidity’/‘aridity’) when considering proxy records of climate change. While the terms are sometimes used interchangeably, moisture availability is determined by both (i) precipitation amount and (ii) temperature, through its influence on potential evapotranspiration. As many palaeoenvironmental proxies reflect changes in this water balance rather than purely precipitation amount, it is important to distinguish between the potential relative influences of precipitation and temperature if those records are to be interpreted in terms of climate mechanisms and/or compared with model outputs. As a case study, we explore how precipitation and temperature have determined moisture availability in South Africa's summer rainfall zone over the last 45 000 years. Using quantitative reconstructions of mean annual temperature, summer rainfall amount and an aridity index, our analysis reveals strong spatiotemporal variability in the relative influences of precipitation and temperature on aridity. Temperature is shown to have exerted a considerable and even dominant influence on moisture availability, resulting in elevated humidity during the last glacial period, despite significant reductions in precipitation amount.

Erratum to: Influence of different GPS receiver antenna calibration models on geodetic positioning - Q. Baire; C. Bruyninx; J. Legrand; E. Pottiaux; W. Aerts; P. Defraigne; N. Bergeot; J. M. Chevalier (GPS Solutions, 2016)

Hydrological variability of major French rivers over recent decades, assessed from gauging station and GRACE observations - L. Chevalier; B. Laignel; N. Massei; S. Munier; M. Becker; I. Turki; A. Coynel; A. Cazenave (Hydrological Sciences Journal, 2014)

Influence of different GPS receiver antenna calibration models on geodetic positioning - Q. Baire; C. Bruyninx; J. Legrand; E. Pottiaux; W. Aerts; P. Defraigne; N. Bergeot; J. M. Chevalier (GPS Solutions, 2014)

Eutrophication as a driver of r ‐selection traits in a freshwater fish - M. Lin; M. Chevalier; S. Lek; L. Zhang; R. E. Gozlan; J. Liu; T. Zhang; S. Ye; W. Li; Z. Li (Journal of Fish Biology, 2014)
This study tested whether eutrophication could influence life‐history traits of a cyprinid, Chanodichthys erythropterus , in 10 Chinese lakes. Using the von Bertalanffy growth model, the asymptotic length ( L ∞ ) and the growth performance index ( I GRO ) were significantly affected by eutrophication. The gonado‐somatic index ( I G ) and relative fecundity ( F R ) were significantly lower in mesotrophic lakes than in eutrophic and hypertrophic lakes. These results indicate that increasing eutrophication affects the life‐history tactics of a freshwater fish.

Air breathing in Magadi tilapia Alcolapia grahami , under normoxic and hyperoxic conditions, and the association with sunlight and reactive oxygen species - O. E. Johannsson; H. L. Bergman; C. M. Wood; P. Laurent; D. G. Kavembe; A. Bianchini; J. N. Maina; C. Chevalier; L. F. Bianchini; M. B. Papah; R. O. Ojoo (Journal of Fish Biology, 2014)
Observations of the Magadi tilapia Alcolapia grahami in hot, highly alkaline Lake Magadi revealed that they air breathe not only during hypoxia, as described previously, but also during normoxia and hyperoxia. Air breathing under these latter conditions occurred within distinct groupings of fish (pods) and involved only a small proportion of the population. Air breathing properties (duration and frequency) were quantified from video footage. Air breathing within the population followed a diel pattern with the maximum extent of pod formation occurring in early afternoon. High levels of reactive oxygen species ( ROS ) in the water may be an irritant that encourages the air‐breathing behaviour. The diel pattern of air breathing in the field and in experiments followed the diel pattern of ROS concentrations in the water which are amongst the highest reported in the literature (maximum daytime values of 2·53–8·10 µM H 2 O 2 ). Interlamellar cell masses ( ILCM ) occurred between the gill lamellae of fish from the lagoon with highest ROS and highest oxygen levels, while fish from a normoxic lagoon with one third the ROS had little or no ILCM . This is the first record of air breathing in a facultative air‐breathing fish in hyperoxic conditions and the first record of an ILCM in a cichlid species.

Debris-flow susceptibility analysis using fluvio-morphological parameters and data mining: application to the Central-Eastern Pyrenees - G. G. Chevalier; V. Medina; M. Hürlimann; A. Bateman (Natural Hazards, 2013)

Transepithelial potential in the Magadi tilapia, a fish living in extreme alkalinity - Chris M. Wood; Harold L. Bergman; Adalto Bianchini; Pierre Laurent; John Maina; Ora E. Johannsson; Lucas F. Bianchini; Claudine Chevalier; Geraldine D. Kavembe; Michael B. Papah; Rodi O. Ojoo (Journal of Comparative Physiology B, 2012)

Effect of cytochrome P450 2C19 genotype on voriconazole exposure in cystic fibrosis lung transplant patients - Maud Berge; Romain Guillemain; David A. Trégouet; Catherine Amrein; Veronique Boussaud; Patrick Chevalier; Agnes Lillo-Lelouet; Christine Le Beller; Pierre Laurent-Puig; Philippe H. Beaune; Eliane M. Billaud; Marie-Anne Loriot (European Journal of Clinical Pharmacology, 2011)

Appearance of cuboidal cells in relation to salinity in gills of Fundulus heteroclitus, a species exhibiting branchial Na+ but not Cl− uptake in freshwater - Pierre Laurent; Claudine Chevalier; Chris M. Wood (Cell and Tissue Research, 2006)

Complexity of the human whole saliva proteome - C. Hirtz; F. Chevalier; D. Centeno; J. C. Egea; M. Rossignol; N. Sommerer; Deville de Périère (Journal of Physiology and Biochemistry, 2005)

Lack of mtDNA differentiation among hamlets ( Hypoplectrus , Serranidae) - P. P. Chevalier Monteagudo; M. Solignac; E. Garca-Machado (Marine Biology, 2004)

Rapid molecular typing method for the reliable detection of Asiatic black truffle ( Tuber indicum ) in commercialized products: fruiting bodies and mycorrhizal seedlings - D. Mabru; C. Dupré; J. P. Douet; P. Leroy; C. Ravel; J. M. Ricard; B. Médina; M. Castroviejo; G. Chevalier (Mycorrhiza, 2001)

Intracellular vesicular trafficking in the gill epithelium of urea-excreting fish - P. Laurent; C. M. Wood; Y. Wang; S. F. Perry; K. M. Gilmour; P. Part; C. Chevalier; M. West; P. J. Walsh (Cell and Tissue Research, 2001)

A sensitive mapping strategy for monitoring the reproducibility of glycan processing in an HIV vaccine, RGP-160, expressed in a mammalian cell line - N.T. Tran; M. Taverna; A.H. Merry; M. Chevalier; G. Morgant; C. Valentin; D. Ferrier (Glycoconjugate Journal, 2000)

Critical power of knee extension exercises does not depend upon maximal strength - J. M. Le Chevalier; H. Vandewalle; C. Thépaut-Mathieu; M. Pujo; B. Le Natur; J. F. Stein (European Journal of Applied Physiology, 2000)

Socioeconomic status, social mobility and cancer occurrence during working life: a case–control study among French electricity and gas workers - B. Marshall; A. Chevalier; C. Garillon; M. Goldberg; F. Coing (Cancer Causes & Control, 1999)

Peak power and pulmonary oxygen uptake during knee extension exercise ? comparisons among different incremental protocols - J. M. Le Chevalier; H. Vandewalle; J. M. Vallier; M. Wolff; J. F. Stein (European Journal of Applied Physiology, 1998)

Electromyogram as an indicator of neuromuscular fatigue during incremental exercise - C. Hanon; C. Thpaut-Mathieu; C. Hausswirth; J. M. Le Chevalier (European Journal of Applied Physiology, 1998)

Antibacterial Activity of 5-Aminoorotic Acid Derivatives - M. El Kolli; A. Coulibaly; J. Chevalier; J. Barbe; A. Crémieux (Current Microbiology, 1998)

A new mutation, 3905insT, accounts for 4.8% of 1173 CF chromosomes in Switzerland and causes a severe phenotype - M. Hergersberg; Jaya Balakrishnan; Thomas Bettecken; Francoise Chevalier-Porst; Christian Brägger; René Burger; Inge Einschenk; Sabina Liechti-Gallati; Michael Morris; Daniel Schorderet; Francine Thonney; Hans Moser; et al. (Human Genetics, 1997)